2017
DOI: 10.1016/j.psychsport.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and achievement goals revisited: The 3 × 2 achievement goal framework

Abstract: Design: Cross-sectional.Method: We examined self-reported perfectionistic strivings, perfectionistic concerns, and the 3 × 2 achievement goals in 136 junior athletes (mean age 17.0 years).Results: The results of structural equation modeling showed that PS were positively associated with task-, self-, and other-approach goals and negatively with task-and selfavoidance goals. In contrast, PC were positively associated with task-, self-, and otheravoidance goals and negatively with task-and self-approach goals.Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
9
0
4
Order By: Relevance
“…The two dimensions broadly reflect either the energising or the critical, self-evaluative components of the construct, and because of this, each has a tendency to demonstrate a different pattern of association with a range of cognitive, affective and behavioural outcomes (González-Hernández, Capilla and Gómez-López, 2019; Haraldsen, Halvari, Solstad, Abrahamsen and Nordin-Bates, 2019; Stoeber and Otto, 2006). Whereas perfectionistic strivings are often associated with adaptive processes and outcomes, the dimension of perfectionistic concerns is consistently associated with maladaptive processes and outcomes (Madigan et al, 2017). In a recent review and reanalysis of existing evidence into perfectionism in sport, exercise, and dance, Hill, Mallinson-Howard, Madigan and Jowett (2019) concluded that perfectionistic strivings dimension is complex and ambiguous and that "this dimension (PS) would be unambiguously adaptive for athletes, dancers, and exercisers if it was not correlated with PC, but it typically is" (p. 29).…”
Section: Introductionmentioning
confidence: 99%
“…The two dimensions broadly reflect either the energising or the critical, self-evaluative components of the construct, and because of this, each has a tendency to demonstrate a different pattern of association with a range of cognitive, affective and behavioural outcomes (González-Hernández, Capilla and Gómez-López, 2019; Haraldsen, Halvari, Solstad, Abrahamsen and Nordin-Bates, 2019; Stoeber and Otto, 2006). Whereas perfectionistic strivings are often associated with adaptive processes and outcomes, the dimension of perfectionistic concerns is consistently associated with maladaptive processes and outcomes (Madigan et al, 2017). In a recent review and reanalysis of existing evidence into perfectionism in sport, exercise, and dance, Hill, Mallinson-Howard, Madigan and Jowett (2019) concluded that perfectionistic strivings dimension is complex and ambiguous and that "this dimension (PS) would be unambiguously adaptive for athletes, dancers, and exercisers if it was not correlated with PC, but it typically is" (p. 29).…”
Section: Introductionmentioning
confidence: 99%
“…When the recent studies conducted within the scope of the Achievement Goal Theory are examined, the studies testing the validity and reliability of the 3 x 2 Model in different samples come to the front. The studies conducted in Hong Kong (Ning, 2018), Austria (Lüftenegger et al, 2016) and Philippines (David, 2014) with undergraduate students; in Spain (Méndez-Giménez, Cecchini-Estrada, Fernández-Río, Saborit, & Méndez-Alonso, 2017) with high school students; in Taiwan with junior high and elementary school students (Wu, 2012); in France (Mascret Elliot & Cury, 2017) and Turkey (Yerdelen & Padar, 2017) with teachers; in France (Mascret, Elliot, & Cury, 2015) and the United Kingdom (Madigan, Stoeber, & Passfield, 2017) in sports and in the United States in the online learning environment (Yang, Taylor, & Cao, 2016). It is seen that the most appropriate model measuring goal orientations is the 3 x 2 Achievement Goal Model.…”
Section: Introductionmentioning
confidence: 99%
“…Given the multidimensional conception of perfectionism in contexts of practice of physical-sporting activity (Madigan, Stoeber, & Passfield, 2017;Stumpf & Parker, 2000), the last two decades have seen a noticeable increase in studies that have tried to determine the association between its different dimensions, and the cognitive, emotional, and/or behavioural aspects that motivate the practice of physical activity (Hill, Hall, Appleton, & Kozub, 2008;Longbottom, Grove, & Dimmock, 2010). PA is regarded as functional when it is positively (and as adaptive efforts) associated with aspects such as self-efficacy, self-confidence, planning, and persistence in the physical activity (Moore et al, 2018), and dysfunctional when linked to uncertainty regarding execution, fear of failure, anxiety, and avoiding physical activity (Flett & Hewitt, 2005).…”
mentioning
confidence: 99%